Static cold storage compared with normothermic machine perfusion of the liver and effect on ischaemic-type biliary lesions after transplantation: a propensity score-matched study. Issue 9 (24th May 2021) - Fodor, M; Cardini, B; Peter, W; Weissenbacher, A; Oberhuber, R; Hautz, T; Otarashvili, G; Margreiter, C; Maglione, M; Resch, T; Krendl, F; Meszaros, A T; et al.
Abstract: Background: Given the susceptibility of organs to ischaemic injury, alternative preservation methods to static cold storage (SCS), such as normothermic machine perfusion (NMP) are emerging. The aim of this study was to perform a comparison between NMP and SCS in liver transplantation with particular attention to bile duct lesions. Methods: The outcomes of 59 consecutive NMP-preserved donor livers were compared in a 1 : 1 propensity score-matched fashion to SCS control livers. Postoperative complications, patient survival, graft survival and bile duct lesions were analysed. Results: While patients were matched for cold ischaemia time, the total preservation time was significantly longer in the NMP group (21 h versus 7 h, P < 0.001) . Patient and graft survival rates at 1 year were 81 versus 82 per cent ( P = 0.347) and 81 versus 79 per cent ( P = 0.784) in the NMP and SCS groups, respectively. The postoperative complication rate was comparable ( P = 0.086); 37 per cent NMP versus 34 per cent SCS patients had a Clavien-Dindo grade IIIb or above complication. There was no difference in early (30 days or less) (NMP 22 versus SCS 19 per cent, P = 0.647) and late (more than 30 days) (NMP 27 versus SCS 36 per cent, P = 0.321) biliary complications. However, NMP-preserved livers developed significantly fewer ischaemic-type bile duct lesions (NMP 3 versus SCS 14 per cent, P = 0.047). Conclusion: The use of NMP allowed for a significantly prolonged organ preservation with a lower rate of observed ischaemic-type bile duct lesions. Abstract : The aim of this analysis was to perform a comparison between normothermic machine perfusion (NMP) and static cold storage (SCS) in liver transplantation (LT) with particular attention to bile duct lesions. The use of NMP prior to LT allowed for a significantly prolonged organ preservation. While patient and graft survival between NMP and SCS where equal, a lower rate of ITBL and shorter length of stay as observed.